Effects of Guava Juice (Psidium guajava L.) Addition at Different Concentrations on Edamame Yogurt - Ni'matul, Fina Azizah; Manan, Abdul; Pribadi, Eko Teguh (Universitas Pakuan, 2024)
Edamame (Glycine max L. Merrill) is a functional food rich in plant-based protein that can serve as an alternative to animal protein sources. Its potential has led to the development of edamame yogurt, a lactose-free fermented product suitable for individuals with lactose intolerance. However, the characteristic “beany” flavor of soy-based products tends to reduce consumer acceptance. To improve sensory quality, taste, and nutritional value, guava (Psidium guajava L.) juice was incorporated into edamame yogurt formulations. This study aimed to evaluate the effects of varying guava juice concentrations on the organoleptic, physical, chemical, and antioxidant properties of edamame yogurt. The experiment employed a completely randomized design (CRD) consisting of four treatments with five replications, corresponding to guava juice concentrations of 0%, 15%, 25%, and 35%. Statistical analyses were conducted using One-Way ANOVA followed by the Duncan test to identify significant differences. The findings revealed that guava juice addition significantly influenced sensory attributes, physicochemical characteristics, and antioxidant activity. The 15% guava juice formulation was most preferred by panelists based on taste, aroma, and texture evaluation. The 25% guava concentration yielded optimal physical and chemical quality, as indicated by syneresis (2.19%), lactic acid content (0.016%), and a pH value of 4.0, consistent with Indonesian National Standards (SNI). Moreover, the highest antioxidant activity (83.55%) was recorded in the yogurt with 35% guava juice concentration. Overall, these results demonstrate that guava juice supplementation enhances both the functional and sensory qualities of edamame yogurt, offering a promising innovation for plant-based fermented foods. Future studies should optimize the use of stabilizers such as gelatin or carrageenan to improve textural consistency while maintaining the nutritional and bioactive benefits of guava fortification.